Technological Features of Manufacturing of the Golden Horde Non-Glazed Ceramics from Bagaevka Settlement - Igor V. Volkov; Leonard F. Nedashkovsky (Археология евразийских степей)
Bagaevka settlement neighbours the large Ukek and a small town, situated on the site of Hmelevka I settlement. This fact suggests that there was most likely no own commercial production of pottery for sale on the market, at least there is no unambiguous evidence of this at the Bagaevka settlement. The bulk of the pottery was most likely produced in neighbouring city and town, and some was brought from more distant urban settlements and perhaps even from the rural settlements of Ulus Jochi. The range of wares is generally homogeneous in all steppe cities, and most of the fragments in the layer belong to water vessels (reflecting an unequivocal dominance in terms of volume in litres), these are humchas, large- and medium-sized jugs. All of them were made on the potter’s wheel with spiral-tourniquet modelling (РФК‑3‑4). Micro-region pottery is characterized by the presence of natural impurities of various sizes fragments of gaize and fine sand. Firing is continuous or unimpressive three- or five-layered, from yellow to red-brown, but the common feature for the region is beige shades. Burnished and non-burnished ceramics are represented almost in equal quantities; degree of negligence of burnishing is such that it is often difficult to establish the fact of its existence. Just here burnishing with strips lighter than the main surface is considerably presented. A part of small wares is covered with red-brown engobe of intense colour which is significantly represented only in the Madzhar and Saraychik complexes. Formally the same group includes the wares of the Bolgar Ulus (without local impurities, with more impressive three-layer firing or without it, with horizontal burnishing, etc.) and more southern parts of the Lower Volga region (with a greater concentration of fine sand, whitish efflorescence on a surface, etc.). The ceramics of conditional second local group with impressive signs of pulling on a potter’s wheel (RFK‑5‑7) isn’t numerous. These are smaller vessels (mainly jars) with similar features of pottery paste. The pottery of this group is more often covered with red-brown engobe, as well as reliably local Ukek sphere-cone vessels. It is most likely that this group was delivered from Ukek. Some pulled vessels have signs of production in the more southern areas of the Lower Volga region. The problem of distinguishing signs of small centres of pottery production in the micro-region still remains.